Improving construction industry through Integrated Project Delivery (IPD) - Abdul Rahim, Syukran; Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar (Innovacia Sdn Bhd, 2015)
Construction industry has long been plagued by the fragmentation issue that has been passed along from one generation to another.Due to that problem, a number of issues have recently arisen in current construction methods, such as reworks, time delay, rising costs, lack of communication and coordination, and wastages.This paper, through literature review aims to highlight this fragmentation issue and clarify how far it affects to the construction project delivery process.Suggestion on how an Integrated Project Delivery (IPD) approach for design and construction process in order to minimise the fragmentation issue will be concluded.